ISSUES OF POWERS DEMARCATION IN THE ENVIRONMENT PROTECTION SPHERE BETWEEN STATE POWER BODIES - L. Tikhomirova (Russian Journal of Economics and Law)
The article investigates and classifies the issues connected with power demarcation in environment protection sphere between state power bodies. The main reasons for their existence are defined.